2020
DOI: 10.35838/jrap.v7i02.1535
|View full text |Cite
|
Sign up to set email alerts
|

Karakter Eksekutif, Profitabilitas, Leverage, dan Komisaris Independen Terhadap Tax Avoidance Dengan Kepemilikan Institusional Sebagai Variabel Moderasi

Abstract: ABSTRACT        This study aimed to examine and analyze the executive characters, profitability, leverage and independent commissioners on tax avoidance, and the effect of character executive, profitability, leverage and independent commissioners on tax avoidance with institutional ownership as a moderating variable. The population in this study is the Manufacturing Companies in the Industrial Consumer Goods Sector listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The sample in this study is onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
2
2
0
2
Order By: Relevance
“…As a result, the corporation will have to pay less taxes. The findings are consistent with Handayani (2018), Hermawan et al (2021) that profitability affects tax avoidance but contrary to Aulia & Purwasih (2023), Rahmawati & Nani (2021), Prasatya et al (2020).…”
Section: Hypothesis Testingsupporting
confidence: 80%
See 2 more Smart Citations
“…As a result, the corporation will have to pay less taxes. The findings are consistent with Handayani (2018), Hermawan et al (2021) that profitability affects tax avoidance but contrary to Aulia & Purwasih (2023), Rahmawati & Nani (2021), Prasatya et al (2020).…”
Section: Hypothesis Testingsupporting
confidence: 80%
“…Thus, it can be concluded that institutional ownership has a significant role in determining policies related to effective tax levels. Prasatya (2020) research results show that institutional ownership can moderate the profitability of tax avoidance. Businesses that generate large profits must also be prepared to face large tax deferrals as well, where institutional investors can prevent agents from carrying out tax avoidance practices because of the supervision carried out so that management carries out correct tax procedures.…”
Section: Institutional Ownership As a Moderating Variablementioning
confidence: 84%
See 1 more Smart Citation
“…Berbanding terbalik, hasil bahwa leverage berpengaruh negatif disebutkan oleh (Dewi & Noviari, 2017). Prasatya et al (2020) menyebutkan bahwa leverage berpengaruh terhadap tax avoidance. Bertolak belakang dengan hasil sebelumnya, hasil penelitian Rifai & Atiningsih (2019) menjelaskan bahwa leverage tidak berpengaruh terhadap tax avoidance.…”
Section: Pendahuluanunclassified
“…Hal ini bertentangan oleh hasil penelitian Ayuningtyas & Sujana (2018) bahwa profitabilitas berpengaruh negatif terhadap tax avoidance selaras dengan penelitian (Susanti, 2018). Prasatya et al (2020) menyebutkan bahwa profitabilitas tidak berpengaruh terhadap tax avoidance.…”
Section: H2 : Capital Intensity Berpengaruh Negatif Terhadap Tax Avoi...unclassified